Analisis Kepuasan Orangtua Dalam Sistem Pendidikan Ponpes Dengan Pendekatan Servqual dan Structural Equation Modelling (SEM) - Manao, Ibnu Afandi; Khairul, Khairul; Helmandi, Asrul; Pohan, Muhammad Zainal Arifin; Sumiran, Sumiran (Universitas Labuhanbatu, 2026)
This study aims to analyze parents' satisfaction with the educational system of Islamic boarding schools using the Service Quality (SERVQUAL) and Structural Equation Modelling (SEM) approaches. The increasing number of Islamic boarding schools and the growing public demand for quality educational services require educational institutions to provide optimal services. This research employed a quantitative method by collecting data through questionnaires distributed to parents of students at Tahfidz Darul Qur’an Islamic Boarding School. The service quality dimensions analyzed include tangibles, reliability, responsiveness, assurance, and empathy. The data were analyzed using SEM to examine the relationship between service quality dimensions and parents’ satisfaction. The results indicate that service quality has a positive influence on parents’ satisfaction. Several SERVQUAL dimensions significantly contribute to increasing satisfaction, particularly assurance and empathy. These findings suggest that improving educational service quality, including facilities, communication, and educator competence, plays an important role in enhancing parents’ satisfaction. This study is expected to provide insights for Islamic boarding school management in developing strategies to improve educational service quality sustainably.